The practicum component in the Foreign Language Teacher Education Program in Villa Clara, Cuba: achievements and affordances for improvement - Camacho Delgado, Dr. C. Alfredo Andrés (Transformación, 2021)
Objective: In pre-service teacher education, the practicum component may foster the highest level of content integration. The aim of this article is to explore the results that were attained through a study of a cohort of student teachers belonging to Plan D, to explain, on that basis, how this component has been conceived for Plan E in the Foreign Language Teacher Education Program in Villa Clara, Cuba. Methods: Given the nature of the problem that is investigated, a qualitative approach has been adopted (Sampieri, Fernández, & Batista, 2010, pp.10-16). Consequently, the following empirical methods and techniques were applied: a questionnaire, content analysis, focus group, and participant observation. Result: The student teachers value positively their experiences during the practicum, in terms of satisfaction for the results attained, and they acknowledge the role of subjects like Psychology, Pedagogy and General Didactics in preparing them to teach, as well as the work of mentors. In addition, they show opinions about the contextual challenges that they had to face when teaching English at school following communicative language teaching, similar to studies that have been conducted in third world countries around the world. Conclusion: Drawing on the study conducted and theoretical systematization, the following hypothesis has been stated: We believe that future practicum results with Plan E should be qualitatively better, given the practicum curriculum improvement; if the program continues to strengthen logistic conditions, mentors’ preparation and the application of a specific didactics for this component; and if prioritized attention is paid to promoting reflection about contextual school issues, having to do with classroom management.